Stress related factors due to the zoonotic risk among veterinarians in Pakistan - Ajaz, Rahmeen; Robiana Modjo (Jurnal Lentera Kesehatan Masyarakat, 2025)
Veterinarians are at increased risk of occupational stress due to frequent exposure to zoonotic diseases and challenging work environments. This study aimed to investigate the relationship between zoonotic exposure, job control, and social support with stress levels among veterinarians in Pakistan. The primary objective was to examine whether higher exposure to zoonotic risks is associated with increased stress, and whether limited job control and low social support further contribute to elevated stress levels. A cross-sectional study design was employed, involving 110 veterinarians from various regions of Pakistan, including urban and rural areas. Data were collected using a structured questionnaire that included the validated Perceived Stress Scale (PSS- 10) and additional items measuring frequency of zoonotic exposure, job control, and social support. Descriptive analysis, cross-tabulations, and Chi-square tests were used to explore associations, and odds ratios were calculated to measure the strength of these relationships. The results revealed that veterinarians with more frequent zoonotic exposure had significantly higher stress levels (p = 0.041, OR = 3.25). Similarly, low job control (p = 0.037, OR = 4.37) and low social support (p = 0.047, OR = 3.12) were significantly associated with increased stress. These findings underscore the combined impact of biological and psychosocial risks in veterinary practice and suggest actionable recommendations including improving access to personal protective equipment (PPE), enhancing job autonomy, and strengthening mental health support systems. This study highlights the urgent need for targeted interventions such as improved PPE availability, better workplace autonomy, enhanced hygiene practices, and structured peer support systems. It contributes new knowledge to the limited literature in Pakistan and offers practical recommendations for improving occupational health among veterinary professionals.